ENERGY METABOLISM IN BLOOD ERYTHROCYTE AT IONIZING IRRADIATION AND AFTER USING OF 4-BUTANOLIDES VAS-167 (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
It has been established that ionizing irradiation is characterized by a statistically reliable decrease in ATP concentration and sharp increase in AMP level in blood erythrocytes, accompanied by a significant alteration of ATP/ADP, ATP/AMP coefficient ratios and energetic charge. After application of 4-butanolides VAS-167 an expressed tendency to normalization of all studied indices is observed which testifies to a definite biological activity of the mentioned compound.
Keywords: ATP concentration; blood erythrocytes; ionizing irradiation; 4-butanolides VAS-167